Pengaruh Paritas dan Sumber Informasi Terhadap Kehamilan Resiko Tinggi pada Ibu Hamil di Kecamatan Panyabungan - Yusuf, Susi Febriani (Universitas Aufa Royhan, 2019)
Based on the Demographic and Health Survey of Indonesia (SDKI) in 2012, it showed that the maternal mortality rate in Indonesia had reached 228 per 100,000 live births. Ironically with the latest data, there has been an increase in MMR of 359 per 100,000 live births. The research used observational analytic quantitative method with sectional design. the population in this study were all pregnant women in the District of Panyabungan Barat. The sampling technique was total sampling with a total of 57 pregnant women. The data were gathered by using questionnaires abd process and analyzed by using chi square test. The result of the research showed that there was the influence parity and information source to high risk pregnancy. Based on the results of this study, it is known that very high-risk pregnancies for pregnant women in the District of Panyabungan Barat in 2018. So it is advisable for health workers to educate pregnant women about high-risk pregnancy.